Three-component reactions of aromatic amines, 1,3-dicarbonyl compounds, and α-bromoacetaldehyde acetal to access N-(hetero)aryl-4,5-unsubstituted pyrroles - Huang, Wenbo; Wang, Kaimei; Liu, Ping; Li, Minghao; Ke, Shaoyong; Gu, Yanlong (Beilstein Journal of Organic Chemistry, 2020)
N-(Hetero)aryl-4,5-unsubstituted pyrroles were synthesized from (hetero)arylamines, 1,3-dicarbonyl compounds, and α-bromoacetaldehyde acetal by using aluminum(III) chloride as a Lewis acid catalyst through [1 + 2 + 2] annulation. This new versatile methodology provides a wide scope for the synthesis of different functional N-(hetero)aryl-4,5-unsubstituted pyrrole scaffolds, which can be further derived to access multisubstituted pyrrole-3-carboxamides. In the presence of 1.2 equiv of KI, a polysubstituted pyrazolo[3,4-b]pyridine derivative was also successfully synthesized.
Keywords: acid catalyst; [1 + 2 + 2] annulation; KI; pyrazolo[3,4-b]pyridine; pyrroles

(untitled) - O’Hagan, D. (Nat. Prod. Rep., 2000)

(untitled) - Walsh, C. T.; Garneau-Tsodikova, S.; Howard-Jones, A. R. (Nat. Prod. Rep., 2006)

(untitled) - Trost, B. M.; Dong, G. (Org. Lett., 2007)

(untitled) - Lindel, T.; Hochgürtel, M.; Assmann, M.; Köck, M. (J. Nat. Prod., 2000)

(untitled) - Khajuria, R.; Dham, S.; Kapoor, K. K. (RSC Adv., 2016)

(untitled) - Osman, N. A.; Ligresti, A.; Klein, C. D.; Allarà, M.; Rabbito, A.; Di Marzo, V.; Abouzid, K. A.; Abadi, A. H. (Eur. J. Med. Chem., 2016)

(untitled) - Hantzsch, A. (Ber. Dtsch. Chem. Ges., 1890)

(untitled) - Leonardi, M.; Estévez, V.; Villacampa, M.; Menéndez, J. C. (Synthesis, 2019)

(untitled) - Knorr, L. (Ber. Dtsch. Chem. Ges., 1884)

(untitled) - Paal, C. (Ber. Dtsch. Chem. Ges., 1885)

(untitled) - Balakrishna, A.; Aguiar, A.; Sobral, P. J. M.; Wani, M. Y.; Almeida e Silva, J.; Sobral, A. J. F. N. (Catal. Rev.: Sci. Eng., 2019)

(untitled) - Bunrit, A.; Sawadjoon, S.; Tšupova, S.; Sjöberg, P. J. R.; Samec, J. S. M. (J. Org. Chem., 2016)

(untitled) - Billedeau, R. J.; Klein, K. R.; Kaplan, D.; Lou, Y. (Org. Lett., 2013)

(untitled) - Andreou, D.; Kallitsakis, M. G.; Loukopoulos, E.; Gabriel, C.; Kostakis, G. E.; Lykakis, I. N. (J. Org. Chem., 2018)

(untitled) - Firoozi, N.; Torres, G. M.; Arndtsen, B. A. (J. Org. Chem., 2016)

(untitled) - Zheng, Y.; Wang, Y.; Zhou, Z. (Chem. Commun., 2015)

(untitled) - Singh, K.; Kabadwal, L. M.; Bera, S.; Alanthadka, A.; Banerjee, D. (J. Org. Chem., 2018)

(untitled) - Herath, A.; Cosford, N. D. P. (Org. Lett., 2010)

(untitled) - Xu, J.; Green, A. P.; Turner, N. J. (Angew. Chem., Int. Ed., 2018)

(untitled) - Chelucci, G. (Coord. Chem. Rev., 2017)

(untitled) - Estévez, V.; Villacampa, M.; Menéndez, J. C. (Chem. Soc. Rev., 2014)

(untitled) - Gulevich, A. V.; Dudnik, A. S.; Chernyak, N.; Gevorgyan, V. (Chem. Rev., 2013)

(untitled) - Estévez, V.; Villacampa, M.; Menéndez, J. C. (Chem. Soc. Rev., 2010)

(untitled) - Ahmad, S.; Alam, O.; Naim, M. J.; Shaquiquzzaman, M.; Alam, M. M.; Iqbal, M. (Eur. J. Med. Chem., 2018)

(untitled) - Winters, M. P.; Sui, Z.; Wall, M.; Wang, Y.; Gunnet, J.; Leonard, J.; Hua, H.; Yan, W.; Suckow, A.; Bell, A.; Clapper, W.; Jenkinson, C.; et al. (Bioorg. Med. Chem. Lett., 2018)

(untitled) - Singh, A.; Mir, N. A.; Choudhary, S.; Singh, D.; Sharma, P.; Kant, R.; Kumar, I. (RSC Adv., 2018)

(untitled) - Thompson, B. B.; Montgomery, J. (Org. Lett., 2011)

(untitled) - Biletzki, T.; Imhof, W. (Synthesis, 2011)

(untitled) - Tao, L.; Wang, Z.-J.; Yan, T.-H.; Liu, Y.-M.; He, H.-Y.; Cao, Y. (ACS Catal., 2017)

(untitled) - Lu, Y.; Fu, X.; Chen, H.; Du, X.; Jia, X.; Liu, Y. (Adv. Synth. Catal., 2009)

(untitled) - Thies, N.; Gerlach, M.; Haak, E. (Eur. J. Org. Chem., 2013)

(untitled) - Zhang, Z.; Zhang, W.; Li, J.; Liu, Q.; Liu, T.; Zhang, G. (J. Org. Chem., 2014)

(untitled) - Kong, H.-H.; Pan, H.-L.; Ding, M.-W. (J. Org. Chem., 2018)

(untitled) - Tracey, M. R.; Hsung, R. P.; Lambeth, R. H. (Synthesis, 2004)

(untitled) - Delayen, A.; Goossens, L.; Goossens, R.; Henichart, J.-P. (Heterocycles, 2005)

(untitled) - Lu, S.; Qi, L.; Li, Z. (Asian J. Org. Chem., 2017)

(untitled) - Wang, M.; Liu, C.; Gu, Y. (Tetrahedron, 2016)

(untitled) - Zhang, M.; Neumann, H.; Beller, M. (Angew. Chem., Int. Ed., 2013)

(untitled) - Zhang, M.; Fang, X.; Neumann, H.; Beller, M. (J. Am. Chem. Soc., 2013)

(untitled) - Chandrasekhar, S.; Patro, V.; Chavan, L. N.; Chegondi, R.; Grée, R. (Tetrahedron Lett., 2014)

(untitled) - Dang, T. T.; Seayad, A. M. (Chem. – Asian J., 2017)

(untitled) - Zeng, J.-C.; Xu, H.; Huang, R.-L.; Yu, F.; Zhang, Z. (Tetrahedron Lett., 2018)

WO Patent - Shishido, Y.; Ohmi, M.; Ando, K. (Azaspiro derivatives as trpm8 antagonists, 2015)

(untitled) - Sun, R.; Liu, Y.; Zhang, Y.; Xiong, L.; Wang, Q. (J. Agric. Food Chem., 2011)

Eur. Patent - Hirth-Dietrich, C.; Sandner, P.; Stasch, J.-P.; Hahn, M.; Follmann, M. (The use of sGC stimulators, sGC activators, alone and combinations with PDE5 inhibitors for the treatment of systemic sclerosis (SSc), 2013)

WO Patent - Boyer, T.; Dodic, N.; Evans, B.; Kirk, B. E. (2,6-disubstituted pyridines and 2,4-disubstituted pyrimidines as soluble guanylate cyclase activators, 2009)

WO Patent - Ushio, H.; Hamada, M.; Watanabe, M.; Numata, A.; Fujie, N.; Takashima, T.; Furukawa, H.; Ando, J. (Amide derivative and use thereof, 2012)

(untitled) - Huang, W.; Liu, C.; Gu, Y. (Adv. Synth. Catal., 2017)

(untitled) - Huang, W.; Chen, S.; Chen, Z.; Yue, M.; Li, M.; Gu, Y. (J. Org. Chem., 2019)

(untitled) - Tu, S.; Wang, Q.; Zhang, Y.; Xu, J.; Zhang, J.; Zhu, X.; Shi, F. (J. Heterocycl. Chem., 2007)

(untitled) - Gunasekaran, P.; Indumathi, S.; Perumal, S. (RSC Adv., 2013)